2023
DOI: 10.3390/horticulturae9030329
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid Induction and Karyotype Analysis of Dendrobium officinale

Abstract: Dendrobium officinale Kimura et Migo is an orchid with both medicinal and edible values and a high economic value. The wild resources of D. officinale are in an endangered state. Compared with the wild D. officinale, cultivated D. officinale exhibits inferior quality and a low content of medicinal components. Polyploid induction is a conventional breeding tool for genome doubling of species, which can effectively increase the total amount of plant components to improve the medicinal efficacy of D. officinale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Similarly, for the top 20 KEGG pathways, the up-regulated DEGs in the BD vs. AD comparison were significantly correlated in protein processing in the endoplasmic reticulum (31), ubiquitin-mediated proteolysis (23), amino sugar and nucleotide sugar metabolism (22), lisosome (20), phagosome (15), and non-alcoholic fatty liver disease (14) (Figure S4b). The down-regulated DEGs in the BD vs.…”
Section: Go and Kegg Of Degs Annotation And Enrichment Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, for the top 20 KEGG pathways, the up-regulated DEGs in the BD vs. AD comparison were significantly correlated in protein processing in the endoplasmic reticulum (31), ubiquitin-mediated proteolysis (23), amino sugar and nucleotide sugar metabolism (22), lisosome (20), phagosome (15), and non-alcoholic fatty liver disease (14) (Figure S4b). The down-regulated DEGs in the BD vs.…”
Section: Go and Kegg Of Degs Annotation And Enrichment Analysismentioning
confidence: 87%
“…Chromosome manipulation is a feasible way to improve the quality traits of Dendrobium species and various ornamental crops [15,16]. Through colchicine treatment, autopolyploids have been induced in various Dendrobium species, namely, D. chrysotoxum [17], D. devonianum [18], D. nobile [19], D. ochreatum [20], and D. officinale [21,22]. Presently, approximately 20 registered hybrids have emerged from both intra-and intersectional hybridization of D. officinale.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that, although most scholars who studied polyploid plants showed gigantism compared to diploid plants, the polyploid plants often showed gigantism in their organs in terms of the external morphology compared to the diploid plants because of changes in the chromosome numbers in the body, for example, enlarged and thicker leaves [24], thicker and stronger stems, and larger flowers and fruits. In leaf epidermal cell morphology, stomatal size and density show signs of polyploidization [25][26][27].…”
Section: Ploidy Identification Of Begonia × Benariensis Polyploidsmentioning
confidence: 99%